2012
DOI: 10.1636/hi11-66.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of prey-specific predatory behavior in a jumping spider (Araneae: Salticidae)

Abstract: Development of prey-specific predatory behavior in a jumping spider (Araneaei Salticidae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Secondly, the prey-specific behaviour has been reported for Y. arenarius capturing morphologically similar insects chosen for the tests (Bartos 2002(Bartos , 2007. Similar prey-specific behaviour was also reported for very young juveniles of Y. arenarius hunting thrips and caterpillars, which suggested that the spiders soon after hatching are able to recognize the prey (possibly without prior experience with the prey) and adopt preyspecific behaviours observed in adult spiders (Bartos 2008;Bartos & Szczepko 2012).…”
Section: Experiments 2 (Natural Prey)supporting
confidence: 55%
See 4 more Smart Citations
“…Secondly, the prey-specific behaviour has been reported for Y. arenarius capturing morphologically similar insects chosen for the tests (Bartos 2002(Bartos , 2007. Similar prey-specific behaviour was also reported for very young juveniles of Y. arenarius hunting thrips and caterpillars, which suggested that the spiders soon after hatching are able to recognize the prey (possibly without prior experience with the prey) and adopt preyspecific behaviours observed in adult spiders (Bartos 2008;Bartos & Szczepko 2012).…”
Section: Experiments 2 (Natural Prey)supporting
confidence: 55%
“…Although a possibility that some of the spiders encountered a prey before the experiments could not be entirely excluded, the method used for collecting the spiders and low prey availability in the field made such encounters with different prey unlikely, as discussed in the methods section in this study and elsewhere (Bartos 2008). Spiders are known to modify their behaviour with age and experience (Bays 1962;Edwards & Jackson 1994;Punzo 2004;Nelson et al 2005;Bartos & Szczepko 2012), but this does not seem to be the case of the spiders used in this study because of a very short time that elapsed from their emergence to capture, and also because some combinations of the cues used for the tests are purely virtual and do not occur in nature (e.g. winged caterpillar-like models with antennae).…”
Section: Innate Predatory Versatilitymentioning
confidence: 96%
See 3 more Smart Citations